Nigeria Pattern of Migration: Issues on Human Sustainable Development - Osayemwenre, Omoroghomwan Blessing; Olayemiomolola, Chris-Obadigie; Faith, Meluwa (Journal of Techno-Social, 2023)
Conventional interpretation on Nigerians’ migration in the 21st Century emphasizes the acceleration and geo-spatial diversification of Nigerians from their home country to other African Countries, Europe, Asia and North America portraying a South-North Migration. Nigeria, like other Africa countries, is often seen and regarded as a country entangled with the problem of mass migration and displacement resulting from poverty, violent conflict, bad governance, insurgency and the dilapidating environmental condition. This perception, to an extent, may likely be untrue when a theoretically informed research is conducted on the pattern of migration in Nigeria. Contradicting the common ideological spread, the pattern of internal and international migration in Nigeria solely does not rest on poverty, conflict and environmental factors, but driven by a prospect for development and social transformation to increase Nigerians’ capability to contribute towards their country’s sustainable development and as such sustain future migration aspiration of the people. This paper x-rays, from a sociological perspective, the pattern, trends and determinant of migration in Nigeria. Relying majorly on secondary information sources, relevant literature on Africa Migration, with Nigeria in mind, were reviewed and criticized bringing out the overlapping knowledge gap in the literature. The review process specifically focused on varied migration process in terms of the scale, pattern and reasons for migration. The precise operational model that justifies the pattern of migration in Nigeria was reviewed and applied to the varied factors responsible for migration. The paper reveals that the diversification of migration streams, changing cause of migration, the predominance of certain categories of migration such as brain-drain all had significant consequence on Nigeria’s sustainable development. The paper concluded that in as much as we want internal and international migration tobe discouraged; the responsibility is laid on government to meet the trans-migration demands of Nigerians.